(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sujana PKW, Wijayanti N. 2022. Phytochemical and antioxidant properties of Syzygium zollingerianum leaves extract. Biodiversitas 23: 916-921. The genus Syzygiumis known as a medicinal plant that has broad bioactive properties due to the abundance of bioactive compounds. Syzygium zollingerianum (Miq.) Amshoff could be considered as one of the important species to study because recent reports indicate that this species only grows in Indonesia and studies on its health benefits are still very limited. This study aimed to determine the phytochemical content of the ethanolic extract of S. zollingeranumleaves and to evaluate its antioxidant activity and cytotoxic effects on Vero cell lines. Phytochemical content was analyzed using spectrophotometry, DPPH assay was used to determine antioxidant activity and MTT assay was carried out to determine its cytotoxicity. The results of the spectrophotometric test showed the presence of phenolic, flavonoids, alkaloids, and tannins in the ethanolic extract of S. zollingeranum leaves. The ability to inhibit free radicals was very strong with antioxidant activity index (AAI) of 68.75 ± 31.386 and IC50 of 0.57 ± 0.211 µg/mL. The results of cytotoxicity examination showed that S. zollingerianumleaves extract has moderate cytotoxicity against Vero cells (101.42 ± 6.823 µg/mL). This study showed that S. zollingerianum leaves extract has great potential as a source of natural exogenous antioxidants and conservation for the sustainability of this plant needs to be considered.